2009
DOI: 10.1111/j.1574-6968.2009.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

The serotype-specific glucose side chain of rhamnose–glucose polysaccharides is essential for adsorption of bacteriophage M102 toStreptococcus mutans

Abstract: Bacteriophage M102 is a virulent siphophage that propagates in some serotype c Streptococcus mutans strains, but not in S. mutans of serotype e, f or k. The serotype of S. mutans is determined by the glucose side chain of rhamnose-glucose polysaccharide (RGP). Because the first step in the bacteriophage infection process is adsorption of the phage, it was investigated whether the serotype specificity of phage M102 was determined by adsorption. M102 adsorbed to all tested serotype c strains, but not to strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 19 publications
(36 reference statements)
0
28
0
1
Order By: Relevance
“…S. mutans strain OMZ 381 is one of a few strains which support propagation of bacteriophage M102 (Delisle & Rostkowski, 1993;Shibata et al, 2009). OMZ 381 was therefore chosen for isolation of phage-resistant mutants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. mutans strain OMZ 381 is one of a few strains which support propagation of bacteriophage M102 (Delisle & Rostkowski, 1993;Shibata et al, 2009). OMZ 381 was therefore chosen for isolation of phage-resistant mutants.…”
Section: Methodsmentioning
confidence: 99%
“…Several mechanisms that render lactic acid bacteria resistant to phage infection have been described: inhibition of phage adsorption, inhibition of DNA injection, restriction modification of phage DNA, and abortive infection (Forde & Fitzgerald, 1999). In the case of S. mutans, nothing is known about the last three mechanisms, but it has been shown that M102 does adsorb also to S. mutans serotype c strains that do not support propagation (Shibata et al, 2009). This suggests that factors different from phage adsorption must determine resistance of S. mutans serotype c strains to infection by M102.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of CRISPR cassettes in 29 S. mutans strains revealed that CRISPR spacers had high sequence similarity with M102, a virulent siphophage specific for S. mutans, suggesting that phage-derived spacers present in these strains likely resulted from M102-like phage attacks (45). Subsequently, it was shown that M102 adheres to phage-sensitive and phage-resistant S. mutans serotype c strains, indicating that factors besides phage adsorption determine resistance of S. mutans serotype c strains to infection by M102 phage (49). Despite these studies that explored the role of CRISPR-Cas systems in S. mutans in conferring phage immunity, recent transcriptome studies suggest other functions that CRISPR-Cas systems might have in S. mutans are poorly understood (50)(51)(52)(53)(54)(55).…”
mentioning
confidence: 99%
“…Each serotype RGP has unique linkages of its glucose side chains (35). It has been shown recently that the glucose side chain of RGP is indispensable for adsorption and infection of S. mutans phage M102 (41).…”
mentioning
confidence: 99%
“…All serotypes of S. mutans produce cell wall rhamnose-glucose polysaccharides (RGPs) consisting of a backbone structure of ␣1,2-and ␣1,3-linked rhamnosyl units with glucose side chains linked to alternate molecules on the cell wall (35,41). Each serotype RGP has unique linkages of its glucose side chains (35).…”
mentioning
confidence: 99%